Considerations on the modeling and control scheme of grid connected inverter with voltage support capability - Brandão, D. I.; Marafão, F. P. [UNESP]; Simões, M. G.; Pomilio, J. A. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper proposes a modeling and control strategy for the operation of distributed generation inverters with voltage support capabilities. The voltage support functionality is based on the injection of reactive current to the grid. Both, modeling and control scheme are based on the definitions from the Conservative Power Theory, which adds some advantages for the control system, e.g., it does not need any kind of reference-frame transformation for defining the current references and, the main power and current terms are conservative, even under non-ideal operating conditions (waveform distortions or frequency deviations). Experimental results are presented in order to validate the system's modeling and inverter controller's design. © 2013 IEEE.
Keywords: Conservative Power Theory; Current control mode; Distributed generation; Reactive compensation; Smart inverters; Voltage support